Energy saving potential through Energy Conservation Building Code and advance energy efficiency measures in hotel buildings of Jaipur City, India - Chedwal, Rajesh; Mathur, Jyotirmay; Agarwal, Ghanshyam Das; Dhaka, Shivraj (Energy and buildings, 2015)
•Calibrated simulation models used for energy saving assessment.•Study implemented building code and advance energy efficiency measures.•Maximum 33% energy saving is possible using building code.•Advance energy efficiency measures save 50.29% energy in four star category hotel.•Economic analysis shows lowest payback for lighting fixtures. Commercial buildings of conventional practices consume significant energy, especially hotel buildings. Therefore, the study aims to estimate energy saving potential in three categories of hotels from Jaipur city, India. Energy Conservation Building Code (ECBC) and advance Energy Efficiency Measures (EEMs) beyond ECBC specifications were implemented such as building envelope, Heating, Ventilation and Air-Conditioning (HVAC) system and lighting system for estimating energy saving potential. Dynamic thermal simulation tool was used for modeling and simulation of existing hotel buildings and simulation models were calibrated against actual energy consumption of study hotels. Implementation of ECBC to hotel Category-1, Category-2 and Category-3 demonstrates energy savings of 37.2%, 18.42% and 25.82%, respectively with payback period of 2.39–6.41 years whereas application of advance EEMs in respective hotels led to increase in energy savings up to 61.75%, 53.92% and 54.61% in respective hotel category with payback period of 4.22–5.11 years. Implementation of ECBC code to existing hotel buildings in Jaipur city can save 27.9GWh/year and with the use of advance EEMs, the city can save 67.04GWh/year of energy. This study concludes that there is significant energy saving potential in hotel buildings in India through implementation of ECBC and other energy efficiency measures.